The National Support Centre for Agriculture as the Trustee of Agricultural Property Stock of the State Treasury in Poland - Litwiniuk, Przemysław (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2018)
On 1 September 2017, the National Support Centre for Agriculture was established and appointed to serve as the Trustee of the Agricultural Property Stock of the State Treasury in Poland. This study profiles the legal relationship of the trust and points out its specifics in reference to state-owned agricultural property. The article includes an evaluation of the assumed legal solutions for the National Support Centre for Agriculture and compares them to the operations of the abolished Agricultural Property Agency.